Contact dermatitis aggravated by other sensitivity in self-medication - Belluco, Paulo Eduardo Silva; Azevedo, Fabíola da Silva Maciel; Lima, Cejana Rebouças Fernandes de; Belluco, Rosana Zabulon Feijó; Reis, Carmélia Matos Santiago (Medicina (Ribeirao Preto), 2021)
Allergic contact dermatitis is an inflammatory, non-infectious skin disease. The treatment is based on the identification and elimination of the causal agent. Cocamidopropyl betaine is a surfactant widely used in products for personal use, especially capillary use. This substance is not present in the Brazilian baseline series. Neomycin is an antibiotic used in topical preparations. We aimed to show a patient who developed na allergy in the scalp and mistakenly self-medicated with a product that contained a substance to which it was even more sensitive. The case is of a woman, 36 years old, evolving for 2 months with pruritic eczema, in areas of capillary and nape implantation. She reported progressive worsening. When contact dermatitis was suspected, a contact test was performed using the Latin American baseline series. At 96 hours (D4) there was mild positivity (+) for cocamidopropyl betaine and strong (++) for neomycin. The positive result for neomycin was intriguing, since the observation of the label of products for personal use did not contain it. In view of the test result, after being questioned again, she confirmed the omission of daily self-medication with neomycin ointment. In conclusion, we showed the allergy to hair products. We reinforced the need for an updated baseline series patch test. Finally, we warned about the risk of self-medication.